Twentieth Century Baptists: People, Places, Principles An Ecumenical High Point?. (2nd January 2021) - Jones, Keith G.
ABSTRACT: In the era of J H Shakespeare the Baptist Union Council was encouraged to enter comprehensive negotiations for greater ecumenical cooperation and, possibly, church union. This was resisted and J H Rushbrooke pointed the Baptist Union Council towards more working together amongst European and world Baptists. Post Shakespeare the Union, through its Council, resisted ecumenical involvement, though it allowed succeeding General Secretaries to engage in some ecumenical encounter. The period 1990–2013 saw a marked shift by Council to ecumenical and theological engagement within the ordinary life of the Council. This was encouraged through an Executive Committee and feeder committees. This era appeared to come to an end in 2013.